A randomized comparison of target-controlled propofol infusion and patient-controlled sedation during ERCP - Mazanikov, Max; Udd, Marianne; Kylänpää, Leena; Mustonen, Harri; Lindström, Outi; Färkkilä, Martti; Halttunen, Jorma; Pöyhiä, Reino (Endoscopy, 2013)
Background and study aims: Propofol is widely used during endoscopic retrograde cholangiopancreatography (ERCP) but high doses are recognized as a risk factor for sedation-related complications. The aim of this study was to compare target-controlled infusion (TCI) with patient self-administration (patient-controlled sedation, PCS) of propofol during ERCP. Propofol consumption, the ease of ERCP performance, and speed of recovery were recorded.Patients and methods: A total of 82 patients undergoing elective ERCP were randomized 1:1 to receive propofol 10 mg/mL using TCI (initial targeted effect-site concentration 2 μg/mL) or PCS (single bolus 1 mL, lockout time set at zero). Alfentanil was administered if signs of insufficient analgesia occurred. Consumption of propofol and alfentanil was recorded, sedation levels and vital signs were monitored, the ease of ERCP performance, speed of recovery, and satisfaction with sedation were evaluated. Results: All procedures were performed without interruptions or major sedation-related complications. The mean (± SD) consumption of propofol was 306 ± 124 mg in the TCI group and 224 ± 101 mg in the PCS group (P = 0.002). Patients in the PCS group recovered faster (P = 0.035). The mean (± SD) consumption of alfentanil was 0.5 ± 0.4 mg in both groups. The combination of propofol and alfentanil was associated with an increased risk of sedation-related adverse events (P = 0.031).Conclusions: No benefits of TCI over PCS could be demonstrated in this study. We recommend considering PCS as a feasible option for propofol administration during ERCP because of its ease of use, high success rate, reduced consumption of propofol, and faster recovery.